A study of clay pore water and sporopollens for characterizing paleoenvironments in the Hebei Plain, Northern China. (1st August 2017) - Niu, Hong; Liang, Xing; Lu, Guoping; Peng, Fei; Jin, Menggui; Gu, Yansheng
Graphical abstract: Highlights: At Hengshui, northern China Plain, 130-m borehole cores were drilled. Sporopollen in sediments, deuterium & oxygen isotope of clay pore water was studied. The clay pore water was of meteoric origin and underwent evaporation. Mean annual temperature and precipitation curves were established. The analyses clarified climate change during the Holocene and Late Pleistocene. Abstract: We developed a clay pore water (CPW) isotopic method for tracing paleoenvironments characterized by sporopollens. The thick clayey layers have the advantage of preserving pore water regardless of whether the water is inherent in the clayey layers or not. Therefore, the clayey layers are a suitable target from which paleoenvironmental information can be extracted. Sediment sporopollens as well as CPW deuterium and oxygen isotopes were investigated in drilling cores obtained from a 130-m borehole at a field site in Hengshui in the North China Plain. Our interpretation of δ 18 O in CPW was consistent with sporopollens climate indices, indicating that CPW was an effective proxy for obtaining paleoenvironmental information. Sporopollens species were abundant in the cores, but the quantity of each species was low. Furthermore, mean annual temperature and precipitation curves were established using a pollen–climatic response surface model. The results indicated two warm-humid periods (5.2–0 m, 22.6–11 m) and one cold-dry period (8.8–6.4 m) in the Holocene as well as two warm-humid periods (90.6–83 m, 110.6–108.2 m) and three cold-dry periods (approximately 40 m, 66.4–56.8 m, approximately 100 m) in the Late Pleistocene. Data derived from the sporopollens and CPW cumulatively elucidate the environmental change in Northern China.